Emergence and Clonal Spread of CTX-M-65-Producing Escherichia coli From Retail Meat in Portugal - Leão, Célia; Clemente, Lurdes; Moura, Laura; Seyfarth, Anne Mette; Hansen, Inge M.; Hendriksen, Rene S.; Amaro, Ana (Frontiers in Microbiology, 2021)
The emergence and dissemination of resistance to third and fourth-generation cephalosporins among Enterobacteriaceae from different sources impose a global public health threat. Here, we characterized by Whole Genome Sequencing four Escherichia coli strains harbouring the blaCTX-M-65 gene identified among 49 isolates from beef and pork collected at retail. The genomic content was determined using the Center for Genomic Epidemiology web tools. Additionally, the prediction and reconstruction of plasmids were conducted, the genetic platform of the blaCTX-M-65 gene was investigated, and the phylogenetic analysis was carried out using 17 other genomes with the same sequence type and harbouring the blaCTX-M-65 gene. All strains harboured blaCTX-M-65, blaOXA1 and blaTEM1B, and one also carried the blaSHV-12 gene. Other resistance genes, namely qnrS2, aac(6')-Ib-c, dfrA14, sul2, tetA and mphA were present in all genomes; the mcr-1.1 gene was identified in the colistin-resistant strains. They belonging to sequence type 2179, phylogenetic group B1, serotype O9:H9, and carried plasmids IncI, IncFIC(FII), and IncFIB. All strains share an identical genetic environment having the IS903 and ISEcp1flanking the blaCTX-M-65 gene. It seems likely that the blaCTX-M-65 gene is located in the chromosome in all isolates based on deep in silico analysis. Our findings showed that the strains are clonally related and belonging to two sub-lineages. This study reports the emergence of CTX-M-65 producing E. coli in Portugal in food products of animal origin. The chromosomal location of the blaCTX-M-65 gene may ensure a stable spread of resistance in the absence of selective pressure.